Resistance to fracture of endodontically treated teeth and sealed with 3 sealers - Freire Meza , Esteban Andrés (2023)
Objective: To determine the resistance to fracture of 60 mandibular premolars endodontically treated and filled with 3 endodontic sealers. Methodology: 60 single-rooted mandibular premolars were used, biomechanical preparation was performed with the ProTaper Next rotary system, with crown down technique, irrigated with 5.25% hypochlorite, filled with single cone technique and subsequently the samples were divided into 4 groups of 15 teeth based on the sealer used. GI: resinous sealer (AH PLUS), GII: bioceramic sealer (Bio C-Sealer), GIII: bioceramic sealer (Bio Root RCS), GIV: negative control. The teeth were incubated at 37ºC for 2 weeks, then they were subjected to compressive forces in a universal testing machine (Asian Test Equipments) at a range of 1mm/min until the root fractured and measured in Newtons. Data were recorded in an Excel spreadsheet for subsequent statistical analysis using one-way ANOVA and Tukey's test. Results: No significant differences were found between the groups evaluated. Conclusions: The final sealing of the endodontic treatment can be carried out with any of the cements studied, without that its resistance to compression will be altered.